Employee participation in organizational change: Investigating the effects of proactive vs. reactive implementation of downsizing in Swedish hospitals - Magnus Sverke; Johnny Hellgren; Katharina Näswall; Sara Göransson; Jan Öhrming (Zeitschrift für Personalforschung (ZfP), 2008)
Whereas employee participation is generally conceived to facilitate implementation of organizational change, only limited research has investigated whether it may reduce the negative effects of downsizing. The present study compares two Swedish hospitals that implemented downsizing in different ways. While there were no major differences in stressors between hospitals, proactive implementation was associated with more employee participation. Moreover, employee participation variables were positively associated with employee work attitudes and well-being at both hospitals. These findings provide insights concerning the importance of a long-term strategic implementation of organizational change. – – Von Mitarbeiterbeteiligung wird gewöhnlich erwartet, dass sie die Implementierung von organisationalem Wandel unterstützt. Dagegen finden sich nur wenige Untersuchungen zur Frage, ob dadurch die negativen Effekte von Downsizing reduziert werden. Die vorliegende Untersuchung vergleicht zwei schwedische Krankenhäuser, in denen Downsizing auf proaktivem bzw. reaktivem Wege implementiert wurde. Zwar finden sich zwischen den Krankenhäusern keine größeren Unterschiede in den Stressoren, aber bei der proaktiven Implementierung waren die Mitarbeiter stärker beteiligt. Mitarbeiterbeteiligung korrelierte positiv mit Arbeitseinstellungen und Wohlbefinden der Mitarbeiter in beiden Krankenhäusern. Die Ergebnisse geben Hinweise auf die Bedeutung der langfristig-strategischen Implementierung von organisationalem Wandel.
Keywords: 330; organizational change; work attitudes; well-being; organizational justice; health care; Krankenhaus; Organisatorischer Wandel; Personalabbau; Mitbestimmung; Stress; Arbeitszufriedenheit; Schweden